2021
DOI: 10.1016/j.bj.2021.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for live, interactive otolaryngology telemedicine: 19-Month experience before and during the COVID-19 pandemic in Taiwan

Abstract: Background Unequal access to healthcare is a global medical problem. Telemedicine, recently made possible by technological advances, may mitigate this inequity. However, the usefulness of telemedicine for procedure-driven disciplines, such as otolaryngology, under infectious conditions (e.g., the COVID-19 pandemic) is unknown. Methods Telemedicine was made legal in Taiwan by an amendment to the Physician Act in 2018. Kaohsiung Chang Gung Memorial Hospital was the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The diagnostic accuracy and effectiveness of empiric therapy provided during TM visits are of particular interest in determining the feasibility of its use in the effective management of patients 14 . A limitation to this type of approach is the need for an adequately trained health care technician to perform diagnostic and minor therapeutic procedures 13 , 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnostic accuracy and effectiveness of empiric therapy provided during TM visits are of particular interest in determining the feasibility of its use in the effective management of patients 14 . A limitation to this type of approach is the need for an adequately trained health care technician to perform diagnostic and minor therapeutic procedures 13 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found that the use of TM with the help of a health technician, who can perform the clinical examination and transmit the data in real time to the specialist, was used mostly for ear diagnoses (52.6%). The remaining diagnoses included throat problems (14.1%) and nasal disorders (13.3%), earwax plug (9.2%), chronic otitis externa (8.1%) and otitis media (8.1%) 15 . The same authors noted that a specialised procedure was not required to diagnose and treat 51% of cases; therefore, they were considered suitable for TM, but the eligibility varied depending on the anatomic site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…performed a retrospective cohort study, looking at the usefulness of telemedicine under infectious conditions in otolaryngology outpatient consultations at a clinic in Taiwan. 2018 legal amendments were performed to further introduce telemedicine in the country, although it has not yet been largely included in otolaryngology routine clinical practice [ 29 ]. While on the one side healthcare can be made more accessible through telemedicine, disadvantages lie in the challenges of the technology itself.…”
Section: Also In This Issuementioning
confidence: 99%
“…conclude that remote, face-to-face, real-time otolaryngology telemedicine service is efficient, time-saving and satisfactory for patients as well as healthcare practitioners despite the limiting but often required specialized procedures in the field. Further technological progress will allow a higher patient eligibility and service level [ 29 ].…”
Section: Also In This Issuementioning
confidence: 99%